2017
DOI: 10.1002/mp.12682
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of GafChromic® EBT3 intrinsic energy dependence with kilovoltage x rays, 137Cs, and 60Co

Abstract: Purpose: To determine experimentally the intrinsic energy response, k bq , of EBT3 GafChromic â radiochromic film with kilovoltage x rays, 137 Cs, and 60 Co in therapeutic and diagnostic dose ranges through direct measurement with an accompanying mathematical approach to describe the physical processes involved. Methods: The EBT3 film was irradiated with known doses using 60 Co, 137 Cs, and 13 NIST-matched kilovoltage x-ray beams. Seven dose levels, ranging from 57 to 7002 mGy, were chosen for this work. Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 41 publications
6
39
1
6
Order By: Relevance
“…The results from this work agree with previous studies indicating that a 20% or larger under‐response compared to 60Co is observed near the BP. A similar maximum under‐response with EBT3 film has also been reported for the RE from a 115.2 MeV/u carbon ion beam and for the film's intrinsic energy response from a M20 x‐ray beam quality . It also appears from the results shown in Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results from this work agree with previous studies indicating that a 20% or larger under‐response compared to 60Co is observed near the BP. A similar maximum under‐response with EBT3 film has also been reported for the RE from a 115.2 MeV/u carbon ion beam and for the film's intrinsic energy response from a M20 x‐ray beam quality . It also appears from the results shown in Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Such a behavior has been previously observed in the work of Hammer et al. where the low‐dose (i.e., 500 mGy) regime response showed evidence of increasing intrinsic film response than that of higher dose regimes across photon energies ranging from 10 to 1250 keV …”
Section: Discussionsupporting
confidence: 75%
“…19,21,22 Accurate dosimetry with these films is challenging, as they are known to have an energy-dependent response at low photon energies. [23][24][25] Eaton and Duck reported differences of up to 6.9% between percent depth dose curves measured with an ionization chamber and Gafchromic EBT film, 19 and up to 8.8% local difference (<10 mm from applicator surface) and 4.8% absolute (>10 mm from applicator surface) difference from the manufacturer (i.e., TARGIT) depth dose curve. They attributed these differences to other experimental uncertainties, such as positioning, rather than film energy dependence.…”
Section: A4 Independent Dose Measurements: Radiochromic Filmmentioning
confidence: 99%
“…Radiochromic films, such as Gafchromic models, have been used in previous studies to investigate the relative and absolute dosimetry of the INTRABEAM system . Accurate dosimetry with these films is challenging, as they are known to have an energy‐dependent response at low photon energies . Eaton and Duck reported differences of up to 6.9% between percent depth dose curves measured with an ionization chamber and Gafchromic EBT film, and up to 8.8% local difference (<10 mm from applicator surface) and 4.8% absolute (>10 mm from applicator surface) difference from the manufacturer (i.e., TARGIT) depth dose curve.…”
Section: Introductionmentioning
confidence: 99%
“…Radiochromic films due to their high spatial resolution, near tissue‐equivalence, and ability to measure two‐dimensional (2D) planar dose are readily used in radiotherapy dosimetry and quality assurance . The latest of EBT‐series radiochromic films, EBT‐XD (Ashland Inc, Bridgewater, NJ, USA) was specifically designed for high‐dose radiotherapy applications, such as stereotactic radiosurgery and stereotactic body radiation therapy.…”
Section: Introductionmentioning
confidence: 99%